Omani Folk Literature and Its Impact on Society - Siddig, Omer (Journal of Cultural Analysis and Social Change, 2025)
Omani folk literature represents a living mirror of the cultural and historical identity of Omani society, reflecting its values, traditions, and worldview through various forms such as Nabati poetry, folktales, proverbs, chants, and performing arts. This literature serves as a repository of collective experiences and a medium for documenting the social, political, and economic transformations Oman has undergone throughout the ages. Folk literature has significantly contributed to strengthening social cohesion by embedding moral and religious values and reinforcing intergenerational bonds through the exchange of stories and proverbs that carry profound wisdom and human experiences. It has also played an educational and awareness-raising role, instilling positive principles such as courage, generosity, and solidarity. Moreover, Omani folk literature has had a notable impact on shaping national consciousness and fostering belonging, as it celebrates heritage, maritime and agricultural traditions, and Oman’s historical role in trade and navigation. With the evolution of Omani society, folk literature has remained a vital tool for preserving cultural identity in the face of globalization, as well as a key pillar in academic studies of heritage and anthropology. Therefore, studying Omani folk literature reveals its central role in nation-building, not merely as a cultural luxury but as a fundamental force in shaping the Omani character and safeguarding its cultural legacy.
Keywords: Littérature – Oman

الخيل في ديوان الشّاعر العماني أبي الفضل (ت 1345 هــ) - البرقاوي, بسام بن بلقاسم (مجلة العلوم الإنسانية (جامعة سبها), 2025)
نهتمّ في هذه الدّراسة بتدبّر قصائد الخيل التي نظمها الشّاعر العماني محمّد بن عيسى بن صالح الحارثي المكنّى بأبي الفضل. وممّا حفّزنا على الاهتمام بهذا الموضوع ندرة الدّراسات التي تصرف الجهد إلى تدبّر وصف الخيل عند هذا الشّاعر وغيره من الشّعراء العمانيين الذين برّزوا في هذا الغرض. ولمّا كان أبو الفضل شاعرا فارسا من فرسان عصره وقائد زمرة الخيّالة في محافظة الشّرقيّة بسلطنة عمان خصّصنا المبحث الأوّل لاستجلاء منزلة الخيل من حياة الشّاعر قبل أن نتدبّرها في شعره وخاصّة في القصائد التي سميّت بـ" الخيليات". وقد تبيّن لنا في ما تبيّن أنّ الخيل سجيّة في وجدان أبي الفضل. فهو قد نشأ عليها وشبّ في بيئة بينها وبين الخيل أسباب وأنساب. ثمّ أتينا بعد ذلك على المدوّنة الشّعريّة فوزّعناها على محورين اثنين: محور لتدبّر خصائص الخطاب الذي يكون فيه الخيل معنى من معاني القصيدة، ومحورًا لتأمّل القصائد التي اقتصر فيها القول على الخيل ولم يجاوزه إلى غيره من المعاني. وبمقاربة إنشائيّة قرأنا نماذج شعريّة أكثرها من قصائد " الخيليات". فخلصنا إلى جملة من النّتائج لعلّ أبرزها أنّ الحارثي كان شاعرا فارسا يسير على خطى المشهورين بنعت الخيل، فيرددّ ما ترسّخ في المدوّنة الشّعريّة التّقليديّة حول الخيل منزلة وصورة. لكنّه في المقابل يأتي في غير قصيدة ببعض ما لم يأت به الأوائل. ومن ذلك أنّه، فضلا عن ذكرها مشتكيا متغزّلا ومفتخرا مادحا وراثيا متألّما وساخرا متهكّما حاورها محاورة طويلة وأنطقها بكلام لم ينطقه بها غيره من الشّعراء. وهو زيادة على وصفها في ساح المسابقات وفي ما طوّف من برور قد استنفر بعض الشّعراء ليتقارضوا معه القول في شأنها فرسا نبع من غير مثال وسُويَّ على غير منوال وفي شأنه فارسا مغوارا لا يشّق له غبار.
Keywords: Littérature – Oman

Preserving Omani Intangible Heritage: A Study of Folktale Authenticity and Classification - Akkawi, Aya Walid Fayyad; Rubai'ey, Fatema; Dineen, Gerard (المجلة العلمية لکلية الآداب جامعة أسيوط, 2025)
To prevent Omani folktale heritage from being lost or distorted, especially in the era of globalization and digitization, and since there is no oral documentation of Omani folktales, there is a need to investigate the authenticity of documented Omani folktales published in print and to classify them based on tale-type. This study attempts to document a comprehensive collection of Omani folktales from existing materials published in or translated into English by developing a classification system based on Hasan El-Shamy‘s established tale-type index. Further, the study aims to assess the authenticity of these folktales by investigating Omani cultural markers found in them and identifying potential distortions or adaptations.
Keywords: Littérature – Oman